Validación del cuestionario “Conociendo a tu hijo(a)” (Ad Hoc. Vaca, S. y Álvarez, B., 2012) para la identificación de niño(a)s de 9 a 10 años con altas capacidades a través de la nominación de padres o madres de familia. - Paladines Costa, María Belén (2014)
The aim of the work is "validate the questionnaire Knowing your child (a) (Ad Hoc) as a diagnostic test in screening phase to identify the child (a) s with high capacity through the nomination of parents or mothers ". Methodology: The research design is not experimental any cross-type, because the data collection was a unique moment, also worked with the factor analysis technique that allows the construct validation. . Population and sample - has three sample types: guest, acceptor and producing data, the latter is 239 subjects. Results: 9 items were eliminated, leaving the final version with 36 items, 10 dimensions and Alpha Cronbach acceptable and high (0.896). Conclusion: The questionnaire obtained through each dimension using factor analysis, and presents an acceptable high reliability and sufficient validity, supported by theoretical and empirical referents. Enough to say that it can be used in screening phase to be supplemented and confirmed by other evidence; after confirmatory factor analysis that requires proof.